PEMANFAATAN SOCIAL LEARNING NETWORK ”EDMODO” DALAM MEMBANTU PERKULIAHAN TEORI BODI OTOMOTIF DI PRODI PTM JPTK FKIP UNS - Basori Basori (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2013)
This research aims to implement social learning network "Edmodo" in the lecture . Specifically, It aims to kmow the contribution of Edmodo in learning activity , to know student perceptions of the completeness of the features and theme of Edmodo , and to know the level of satisfaction with the Edmodo service.This research used descriptive methods . The data were taken using the questionnaire and interview . Data obtained from PTM students who take courses in automotive body with the number of 34person. This research used s a descriptive data analysis .The results shows that : 1 ) There are a significant increase in the contribution of Edmodo in lecture. From the data it can be seen 52.94 % are high , and 38.24 % in the very high category . 2 ) Edmodo feature strongly supports the management of teaching and learning . It appears there are 44.12 % of respondents expressed a very high category , and 35.29 % in the very high category , 3 ) Edmodo theme is very userfriendly , so easy in use . There are 67.65 % of the data is known to the high category , and 14.71 % in the very high category . 4 ) Students feel a high level of satisfaction with the Edmodo service. . From the data it can be seen very high category 61.76 % , and 35.29 % are high.